Earth in Eclipse. - Abram, David (ReVision)
The article argues that the twentieth century has seen an astonishing proliferation of experiential domains, from microscope to nanotechnology and from subatomic physics to the virtual worlds seen in movies. The author says that this proliferation of new worlds and their alluring powers demands the new skill of navigating between worlds. The article traces the fascination with the bodiless spaces made available by digital wizardry and the historical engagement with worlds hidden to Pythagoras and his mystical fascination with mathematics.